Fiscal Policy, Economic Adjustment, and Financial Markets. (Washington, D.C. : International Monetary Fund, 1989)
Edited by Mario Monti, this volume contains the proceedings of a seminar that was held in Milan at the Centre for Financial and Monetary Economics, Universita Luigi Bocconi. Participants included government officials, academicians, and economists; they provide a many-faceted view of fiscal policy at the domestic level and in the broader context of international policy coordination.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet